Temporal and Spatial Analysis of Forward and Backward Microbial Contamination in a Mars Analog Mission - Yair, Yael; Reshef, Leah; Shopen-Gochev, Camelia; Yoffe, Gal; Azulay, Gil; Aharonson, Oded; Sorek-Abramovich, Reut (Frontiers in Astronomy and Space Sciences, 2021)
As human exploration missions to Mars are on the horizon, there is intense emphasis on both ethical and practical aspects of planetary protection. Microbial cross-contamination remains a key issue to address before executing human missions to any planetary body. These issues can be approached today using the advances in molecular metagenomics methods. These methods include rapid and sensitive sequencing platforms for characterizing microbial population. Combined with space analog missions, they provide powerful tools for assessing the challenges associated with space exploration. Here, we designed a protocol to monitor forward and backward contamination events and progression in an analog mission setup of 11-days Mars analog mission in the Ramon crater in Israel. Forward contamination soil samples were collected daily from three sites – two sites in close proximity to the habitat and one reference site. Backward contamination was determined in samples from nitrile gloves of six analog astronauts (AA), before and after extra vehicular activities (EVAs). Temperature, relative humidity and soil composition data were also collected. Environmental DNA samples were extracted in the main habitat and 16S (bacterial) and 18S (eukaryotic, fungal) rRNA gene amplicons were sequenced and analyzed to study the composition of microbial population. Shannon Diversity index analysis and Principal Coordinates analysis (PCoA) of rRNA genes indicated that differences in the diversity and population composition were significant in sites closer to the habitat when compared to a reference site. These samples also demonstrated the introduction of human-associated taxa to the environment. Backward contamination consisted of bacterial taxa found on gloves upon the AAs’ return from EVA and also detected in soil, altogether 44 genera, indicating backward contamination events. To the best of our knowledge, this is the first protocol to utilize advanced molecular technologies to investigate forward and backward contamination in a Mars analog mission.